Trunk musculoskeletal response in maximum voluntary exertions: A combined measurement-modeling investigation. (21st March 2018) - Ghezelbash, F.; El Ouaaid, Z.; Shirazi-Adl, A.; Plamondon, A.; Arjmand, N.
Abstract: Maximum voluntary exertion (MVE) tasks quantify trunk strength and maximal muscle electromyography (EMG) activities with both clinical and biomechanical implications. The aims here are to evaluate the performance of an existing trunk musculoskeletal model, estimate maximum muscle stresses and spinal forces, and explore likely differences between males and females in maximum voluntary exertions. We, therefore, measured trunk strength and EMG activities of 19 healthy right-handed subjects (9 females and 10 males) in flexion, extension, lateral and axial directions. MVEs for all subjects were then simulated in a subject-specific trunk musculoskeletal model, and estimated muscle activities were compared with EMGs. Analysis of variance was used to compare measured moments and estimated spinal loads at the L5-S1 level between females and males. MVE moments in both sexes were greatest in extension (means of 236 Nm in males and 190 Nm in females) and least in left axial torque (97 Nm in males and 64 Nm in females). Being much greater in lateral and axial MVEs, coupled moments reached ∼50% of primary moments in average. Females exerted less moments in all directions reaching significance except in flexion. Muscle activity estimations were strongly correlated with measurements in flexion and extension (Pearson's r = 0.69 and 0.76), but the correlations were very weak in lateral and axial MVEs (Pearson's r = 0.27 and 0.13). Maximum muscle stress was in average 0.80 ± 0.42 MPa but varied among muscles from 0.40 ± 0.22  MPa in rectus abdominis to 0.99 ± 0.29 MPa in external oblique. To estimate maximum muscle stresses and evaluate validity of a musculoskeletal model, MVEs in all directions with all coupled moments should be considered.